The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13019-020-1051-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-year experience with immediate extubation in pediatric patients after congenital cardiac surgery

Abstract: BackgroundIn pediatric cardiac anesthesiology, there is increased focus on minimizing morbidity, ensuring optimal functional status, and using health care resources sparingly. One aspect of care that has potential to affect all of the above is postoperative mechanical ventilation. Historically, postoperative ventilation was considered a must for maintaining patient stability. Ironically, it is recognized that mechanical ventilation may increase risk of adverse outcomes in the postoperative period. Hence, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 17 publications
(17 reference statements)
3
37
1
3
Order By: Relevance
“…The similarity in results suggests that both methods lead to poor talc dispersion on the pleural tissue. In previous work (Laub et al., 2017 ; Baxter et al., 2020 ) we showed that foam drug-delivery systems improve talc pleurodesis. The foams formulations without talc were not able to induce pleural adhesions (Baxter et al., 2020 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The similarity in results suggests that both methods lead to poor talc dispersion on the pleural tissue. In previous work (Laub et al., 2017 ; Baxter et al., 2020 ) we showed that foam drug-delivery systems improve talc pleurodesis. The foams formulations without talc were not able to induce pleural adhesions (Baxter et al., 2020 ).…”
Section: Introductionmentioning
confidence: 81%
“…In previous work (Laub et al., 2017 ; Baxter et al., 2020 ) we showed that foam drug-delivery systems improve talc pleurodesis. The foams formulations without talc were not able to induce pleural adhesions (Baxter et al., 2020 ). It has been hypothesized that the increased efficacy of foam pleurodesis over talc slurry is due to the high volume of foam injected into the pleural cavity, which increases the dispersion of talc on the tissue surface (Laub et al., 2017 ).…”
Section: Introductionmentioning
confidence: 81%
“…The occlusion techniques using this device include classic percutaneous ASD occlusion under fluoroscopy, percutaneous procedure under ultrasound-guidance, and intra-operative device close under ultrasound-guidance [ 1 ]. While percutaneous occlusion is generally considered effective and safe for patients with secundum ASD, limitations with this technique using fluoroscopy include damaging radiation exposure and higher risk for complications for children under 10 years of age [ 1 , 2 ]. The size and rim of the ASD in addition to the size of the occluder are also important to consider when using the percutaneous approach.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that opioid overdose during anesthesia is responsible for a series of adverse effects, such as increased recovery times and opioid induced hyperalgesia, and that opioid overdose also leads to hypotension, having a major impact on perioperative hemodynamic stability [ 66 , 67 , 68 , 69 , 70 , 71 ]. Won et al reported that using SPI monitoring during general anesthesia reduced opioid consumption, improved hemodynamic stability, and reduced postoperative recovery times [ 71 ].…”
Section: Monitoring Techniques For the Nociception-antinociceptionmentioning
confidence: 99%
“… Technologies/parameters used for monitoring the nociception-antinociception balance [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. ANI—analgesia nociception index; qNOX index—index of nociception; SPI—Surgical Plethysmographic Index; NOL index—Nociception Level Index; EEG—Electroencephalography; EMG—Electromyography signal.…”
Section: Figurementioning
confidence: 99%